Subsidiary embeddedness and its influence on the strategic decision-making of the headquarters. - Chee, Li Yee. (2008)
This paper responds to the need for understanding how subsidiary embeddedness, which is defined as a function of three variables – resource interdependence, technological development and communication, can affect the influence the subsidiaries have on the headquarters in the making of strategic decisions.